Influence of dietary organic acid, probiotic and antioxidant on the growth performance and nutrient digestibility in growing rabbit - Chowdhury, R; Rahman , MA; Al Mamun , M (Bangladesh Journal of Animal Science, 2022)
This study was conducted to compare the effects of different feed additives namely, organic acid (citric acid), probiotic (navio plus), and antioxidant (Bio-Sel-E) on the growth performance and nutrient digestibility in growing rabbit to convey a clear message on the use of one specific additive in rabbit diet. Thirty-two crossbred New Zealand White growing rabbit (four to five weeks of age) were randomly assigned to four different groups and reared for a period of fifty six days. Rabbit were fed on green grass (Hymenachne pseudointerrupta) and concentrate mixture (2703 Kcal ME/kg, 16.91 % CP). Additives were added at the top of the concentrate mixture, except for the control group. Compared with the control group, rabbit fed different additives showed 9–13% higher growth rate and 7–11% greater growth velocity; and probiotic supplemented group showed the best result (P<0.05) in terms of FCR value. Carcass weight (%) increased significantly in probiotic supplemented group, but numerically in organic acid and antioxidant supplemented groups compared with control group. Abdominal fat (%) was significantly decreased in organic acid, probiotic and antioxidant supplemented groups compared with control, however, lowest value (%) was recorded in probiotic supplemented group. Probiotic showed significant effect on pH decreasing trend in ingesta sample up to small intestine. Crude protein digestibility co-efficient (%) value was significantly higher in probiotic supplemented group, but numerically in organic acid and antioxidant supplemented groups compared with control group. Overall results indicated that, among the three different additives: organic acid, probiotic and antioxidant, probiotic may be considered as the best one for the better performance and nutrient digestibility in growing rabbit. Bangladesh Journal of Animal Science, 51 (2): 55-61.